Survivability strategy with conditional risk disjunction degree in multi-domain optical networks - ZHAO Ji-hong1; QU Hua2; WANG Li1; MAO Hong-bao1 (Tongxin xuebao)
A survivability strategy based on CRDD（conditional risk disjunction degree） in multi-domain optical networks was provided in order to overcome the defect of the scalability constrained and provide differentiated service. The con- cept of CRDD was provided in this strategy, then the intra-domain virtual links reflection was achieved and the end-to-end work route and backup route to differentiate service reliability were computed with CRDD. The results show that the supported survivability strategy not only can differentiate the service reliability, reduce the blocking probability of service, but also can improve reliability for service requirement by 6.5% on average.